Analisis Implementasi Kepemimpinan Visioner dalam Pengembangan Kinerja Guru PAI melalui Pelatihan SDM di Era 5.0 yang Berdaya Saing dan Berkelanjutan - Nor Fadhilah (Jurnal Pendidikan Islam, 2026)
This research is motivated by the application of visionary leadership in the context of education still facing various challenges, especially in developing teacher performance through competitive and sustainable HR training, as well as being a crucial factor in ensuring the quality of education that is able to produce competent graduates and ready to compete amidst global uncertainty. This study uses the method (library research) the data refers to the literature review. This method goes through 5 stages so that the data is truly credible, namely (1) interpreting the scope of a topic to be reviewed, (2) identifying relevant sources, (3) reviewing literature, (4) writing reviews and (5) applying literature to the study to be conducted. Teachers are not only able to adapt to change but also become an integral part of the competitive and sustainable innovation process. The implementation of visionary leadership in educational leadership in developing sustainable teacher performance in the 5.0 era through competitive HR training, namely visionary educational leaders not only act as managers but also as agents of change who are able to project the future and lead with a clear vision for the development of sustainable teacher performance. The impact of implementing visionary leadership is such as the development of technological and pedagogical competencies, empowerment and sustainable innovation and strengthening collaborative culture. However, there are several challenges that will be faced, such as limited human resources, time, facilities and technology.